81.1k views
5 votes
Derivative of

x^(3)
e^(2x)

User Matroska
by
5.3k points

2 Answers

2 votes


f(x)=x^3e^(2x)\\\\f'(x)=(x^3e^(2x))'\qquad\text{use}\ (f\cdot g)'(x)=f'(x)g(x)+f(x)g'(x)\\\\=(x^3)'(e^(2x))+(x^3)(e^(2x))'\\\\\text{use}\ (x^n)'=nx^(n-1)\ \text{and}\ (e^x)'=e^x\ \text{and}\ f'[g(x)]=f'(g(x))\cdot g'(x)\\\\=3x^2e^(2x)+x^3e^(2x)\cdot2\\\\=\boxed{3x^2e^(2x)+2x^3e^(2x)}

User Nakx
by
5.6k points
5 votes

The derivative of
x^3e^{(2x) can be found using the product rule of differentiation.

Step-by-step explanation:

The derivative of
x^3e^{(2x) can be found using the product rule of differentiation. The product rule states that the derivative of the product of two functions, u and v, is given by the formula (u*v)' = u'v + uv'.

Let
u = x^3 and
v = e^{(2x). Taking the derivatives of u and v, we have:


u' = 3x^2v' = 2e^{(2x)

Using the product rule, the derivative of x^3e^{(2x) is:


(x^3e^((2x)))' = u'v + uv' = (3x^2)(e^((2x))) + (x^3)(2e^((2x))) = 3x^2e^((2x)) + 2x^3e^((2x))

User Zeev Vax
by
5.2k points